Selectin-targeting glycosaminoglycan-peptide conjugate limits neutrophil-mediated cardiac reperfusion injury. Issue 1 (30th October 2020) - Dehghani, Tima; Thai, Phung N; Sodhi, Harkanwalpreet; Ren, Lu; Sirish, Padmini; Nader, Carol E; Timofeyev, Valeriy; Overton, James L; Li, Xiaocen; Lam, Kit S; Chiamvimonvat, Nipavan; Panitch, Alyssa
Abstract: Aims: One of the hallmarks of myocardial infarction (MI) is excessive inflammation. During an inflammatory insult, damaged endothelial cells shed their glycocalyx, a carbohydrate-rich layer on the cell surface which provides a regulatory interface to immune cell adhesion. Selectin-mediated neutrophilia occurs as a result of endothelial injury and inflammation. We recently designed a novel selectin-targeting glycocalyx mimetic (termed DS-IkL) capable of binding inflamed endothelial cells. This study examines the capacity of DS-IkL to limit neutrophil binding and platelet activation on inflamed endothelial cells, as well as the cardioprotective effects of DS-IkL after acute myocardial infarction. Methods and results: In vitro, DS-IkL diminished neutrophil interactions with both recombinant selectin and inflamed endothelial cells, and limited platelet activation on inflamed endothelial cells. Our data demonstrated that DS-IkL localized to regions of vascular inflammation in vivo after 45 min of left anterior descending coronary artery ligation-induced MI. Further, findings from this study show DS-IkL treatment had short- and long-term cardioprotective effects after ischaemia/reperfusion of the left anterior descending coronary artery. Mice treated with DS-IkL immediately after ischaemia/reperfusion and 24 h later exhibited reduced neutrophil extravasation, macrophage accumulation, fibroblast and endothelial cell proliferation, and fibrosis compared to saline controls. Conclusions: Our findings suggest that DS-IkL has great therapeutic potential after MI by limiting reperfusion injury induced by the immune response. Graphical Abstract: